2005
DOI: 10.1097/00131746-200505000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Generalized Anxiety Disorder and a History of Trauma: Somatic Symptom Endorsement

Abstract: The authors investigated the types and rates of trauma exposure and differences in symptom endorsement in a clinical sample of patients diagnosed with generalized anxiety disorder (GAD). Fifty-eight patients with GAD were assessed using the Structured Clinical Interview (SCID) and Trauma Assessment for Adults. In order to explore the relationship between specific traumatic event(s) and clinical presentation, the presence of somatic symptoms associated with GAD, including muscle tension, autonomic hyperactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Although the relationship between exposure to a terrorist attack and GAD symptoms has not been previously examined, our results are consistent with past studies indicating that exposure to trauma, particularly assaultive trauma, is associated with GAD (Brawman-Mintzer, Monnier, Wolitzsky, & Falsetti, 2005; Roemer, Molina, Litz, & Borkovec, 1997), and that an emotional connection to victims is associated with stress symptoms (Dixon, Rehling, & Shiwach, 1993; Terr et al, 1999). Indeed, past studies have shown that disasters may have a negative effect on mental health when a loved one or acquaintance is harmed or when an individual personalizes the event (Dixon et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Although the relationship between exposure to a terrorist attack and GAD symptoms has not been previously examined, our results are consistent with past studies indicating that exposure to trauma, particularly assaultive trauma, is associated with GAD (Brawman-Mintzer, Monnier, Wolitzsky, & Falsetti, 2005; Roemer, Molina, Litz, & Borkovec, 1997), and that an emotional connection to victims is associated with stress symptoms (Dixon, Rehling, & Shiwach, 1993; Terr et al, 1999). Indeed, past studies have shown that disasters may have a negative effect on mental health when a loved one or acquaintance is harmed or when an individual personalizes the event (Dixon et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Dysregulation of the HPA axis has also been associated with panic disorder (Abelson et al, 2007), chronic fatigue syndrome (Van Houdenhove et al, 2009), obsessive-compulsive disorder (Gustafsson et al, 2008), fibromyalgia (Tanriverdi et al, 2007), generalized anxiety disorder (Lenze et al, 2011), and bipolar disorder (Daban et al, 2005). Importantly, stressful life events have been implicated in the onset of each of these disorders (Kendler et al, 1995; Hatcher and House, 2003; Gupta and Silman, 2004; Brawman-Mintzer et al, 2005; Garno et al, 2005; Goodwin et al, 2005; Sarkhel et al, 2011), and dysregulation of the HPA axis may be an etiological link between stress and the subsequent development of pathology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that up to 94.8% of GAD patients were exposed to any trauma (40). GAD may resemble PTSD in this respect and the mechanism of hypocortisolemia may be similar.…”
Section: Discussionmentioning
confidence: 96%